2007
DOI: 10.1007/s00264-006-0267-8
|View full text |Cite
|
Sign up to set email alerts
|

Promising mid-term results of total hip arthroplasties using an uncemented lateral-flare hip prosthesis: a clinical and radiographic study

Abstract: The clinical results after total hip replacements using noncemented stems have shown considerable variability over the years; the design and characteristics of the implant seemed to play a role in explaining this fact. The purpose of this paper is to report the clinical, radiographic and densitometry results of total hip arthroplasties using a stem designed for noncemented implantation and to engage and load the femur proximally. Fifty-eight consecutive patients (62 hips) followed for an average of 4.3 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…This finding was consistent with a postoperative histological phenomenon that hyperostosis was observed near the tip of stems where postoperative stress distribution markedly increased. Meanwhile, bone loss took place around the proximal part of the femoral prosthesis where stress shielding occurred [20]. The presence of the mechanotransduction threshold in the stretch-induced release of PICP may inversely justify a starting point in postoperative bone loss induced by stress shielding.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent with a postoperative histological phenomenon that hyperostosis was observed near the tip of stems where postoperative stress distribution markedly increased. Meanwhile, bone loss took place around the proximal part of the femoral prosthesis where stress shielding occurred [20]. The presence of the mechanotransduction threshold in the stretch-induced release of PICP may inversely justify a starting point in postoperative bone loss induced by stress shielding.…”
Section: Resultsmentioning
confidence: 99%
“…Kim (24) assessed the outcome of a proximally‐coated anatomic stem (IPS, DePuy, Warsaw, IN, USA) in patients with femoral head osteonecrosis and reported 100% survival rate after a mean 8.8‐year follow‐up for cementless THA. Leali and Fetto (18) also reported a 100% survival rate in 48 patients (62 hips) who underwent cementless THA using a metaphyseal loading lateral‐flared hip prosthesis (Revelation hip stem; Encore, Austin, TX, USA) after a mean follow‐up period of 4.3 years. In our series, one patient underwent revision THA and replacement of a broken ceramic liner, and strictly speaking, this was not a faulty femoral stem but rather a ceramic failure.…”
Section: Discussionmentioning
confidence: 99%
“…(25) suggested that the femoral stem below the lesser trochanter is not necessary for a cementless anatomical stem with a lateral flare, and stressed that a proximally fitting implant is sufficient. Leali and Fetto (18) indicated that a cementless anatomical femoral stem required a proximal lateral flare to engage the trochanteric area in order to reproduce the compressive forces between the femoral head and greater trochanter. In a series of biomechanical studies that included Japanese patients with dysplastic hip OA but excluded subjects with idiopathic and ethanol‐induced osteopenia, we indicated that the increment of proximal fit‐and‐fill to the intramedullary femoral canal is important for initial stability under force‐loading condition and possible bone ingrowth that contributes to stem longevity (10,13–15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral flare provides more proximal loading due to the seating of the flare on the lateral cortex of the femur; this feature also provides good stability to the implant and reduces the incidence of migration and subsidence [37][38][39] . This is reflected by the formation of stronger tissues in and around the region.…”
mentioning
confidence: 99%